IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS PANCASILA KELAS IV DI SEKOLAH DASAR - Putra, I Kadek Rindho Resza Putra; Gusti Ngurah Arya Yudaparmita; Nyoman Pancaria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study seeks to examine how character education based on Pancasila is put into practice for Grade IV in Primary Schools (SD) during the 2021-2024 period. Character education rooted in Pancasila values is considered crucial for shaping a younger generation with good personality, ethics, and the ability to behave in accordance with Indonesian norms and culture. The research method used is a literature review (studi literatur). The study results indicate that the application of Pancasila-based character education in Primary Schools has been carried out through the integration of Pancasila values in both learning activities and extracurricular activities. Nevertheless, challenges exist in implementing character education, such as a lack of in-depth understanding from educators regarding the concepts and application of Pancasila values, as well as limited supporting facilities. This research recommends the need for continuous training for educators and support from the government to enhance the effectiveness of Pancasila-based character education in primary schools.